Análise da concepção de professores da educação básica quanto às práticas online de mindfulness no controle da ansiedade - Felipe Cerqueira Castro de Souza (2021)
Introduction: Mindfulness practice has been studied and recognized as a tool to help control anxiety levels through changes in different brain regions. Diseases and disorders related to the teaching profession have been associated with an increase in the level of anxiety and stress among teachers, interfering with their teaching relationships. Searching for simple and non-pharmacological alternatives to control anxiety in teachers can bring benefits to the pedagogical practice and to interpersonal relationships in the school context. Objective: To evaluate the effect of mindfulness training on the anxiety levels of Basic Education teachers and its relationship with teaching practice. Materials and Methods: This is a study that used qualitative and quantitative methodology. Thirteen teachers from the basic education system in Minas Gerais participated in this study, who were divided into two groups, who performed mindfulness training for four weeks. Group 1 (n=7) held a weekly online meeting during four weeks, and they were conducted by an instructor, in addition to performing the practices autonomously during the rest of the week. Group 2 (n=6) carried out training over 28 consecutive online meetings through audio-guide. Teachers' anxiety level was evaluated before and after training through the State-Trait Anxiety Inventory (STAI). To assess mindfulness, the FFMQ-BR questionnaire (Five Facets of Mindfulness Questionnaire - Brazilian version) was used. The FFMQ-BR test was applied on the first and last day of mindfulness training. The literal transcription of the teachers' speeches and reports were qualitatively interpreted using content analysis. Results: The qualitative analysis of the transcripts of speeches indicates that teachers perceived positive changes within their life routine with the mindfulness practice. The statistical data of the STAI did not show significantive differences in the anxiety levels before and after mindfulness practice, although the anxiety state decreased for a few subjects. Final considerations: Teachers realized that online online mindfulness practices, for four weeks, can provide an improvement in anxiety control, which may consequently reflect on their educational practice.